Study The Rate Of Fertility And Risk Factors Of Schizophrenia In Najaf, Iraq - Ajeena Ezzate, H. (University of Eloued جامعة الوادي, 2017)
This study is designed to investigate the main risk factors, which increased the incidence of schizophrenia and the rate of fertility in patients measuring sex hormones (testosterone and estrogen) and prolactin hormone. The aim of study was to evaluate the fertility rate and risk factors of schizophrenia. Blood samples were collected for measuring the hormones from 108 individual divided groups: Patients’ group that contain 78 patients and a control group, which included 30 healthy persons. The results showed that schizophrenia was higher in male than female. Tobacco smoking and family history have significantly risk for most patients which lived in urban areas. There was statistical significance (P ≤ 0.05) in the testosterone hormones between patients group and control group. It is concluded that patients were suffering from hypogonadism, in contrasts with the prolactin hormone, which has been indicated significant increasing of schizophrenia.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 02
Keywords: Schizophrenic Disorders, Fertility Determinants, Sex Steroid Hormones, Tobacco Smoking.